Impact of Attitude Towards Physical Activity and Exercise on Academic Performance of School Students - Yasir Iqbal; Muhammad Badar Habib; Muhammad Adeeb (The Sky)
This research aims to measure the impact of attitude towards physical activity (PA) and exercise on academic performance of school students. The cross sectional and correlational research method were employed. The population of this research was school students of District Sargodha. The total of 307 (154 Male and 153 Female) school students were selected using convenient sampling technique for gathered the data. The attitude towards physical activities questionnaire using to measure the students’ attitude towards PA and exercise; and academic performance was measured through last year academic result of student. The data of this research was analyzed by SPSS (24.0). The results of bivariate correlation revealed positive significant correlation between PA and exercise with academic performance among school students. Students who maximum participate in PA and exercise, they secure better academic marks in their annual exams. Further, the results of linear regression found that PA and exercise significantly impact on academic performance of students. In gender, boys and girls are same in PA and exercise but girls are significantly better than boys in academic performance. This research would be helpful for teachers, physical and sports teachers, psychologist, parents and government agencies for policy making.